Pot the ball? Sovereign wealth funds' outward FDI in times of global financial market turbulence: A yield institutions-based view - K.S. Reddy (Central Bank Review (CBR), 2019)
Noticing the visible hand of state capitalism in global production and value chain system, this study examines the outward foreign direct investment strategy of sovereign wealth funds (SWFs). Leveraging theoretical insights from the conventional political economy and international business literature, the study first conceptualizes a yield institutions-based view—marketization to sustainable competitive advantage—to gain a better understanding of the main purposes and economic and institutional determinants of SWFs. Efforts have been made to deepen the institutions-based perspective of global strategy and introduce it into, establish its relevance to SWFs research. Second, the study presents SWFs' outward FDI patterns and acquisition deals in times of global financial market turbulence. Findings suggest that SWFs' outward FDI choices are primarily determined by institutional transitions, market development and government legitimacy in the home country, thus to invest globally, earn higher economic returns, and secure resources. These choices are firmly motivated toward advanced financial markets, and real estate and infrastructure sectors. Third and last, the study discusses several important implications for state capitalism, policymakers, and sustainable development.
Keywords: F21; F23; G34; M16; 330; Sovereign wealth funds; State capitalism; Outward foreign direct investment; Cross-border mergers and acquisitions; Global financial crisis; Institutions-based view